Analisis Kepribadian Tokoh Utama dalam Novel Jembatan Pensil Karya Rudy Gunawan FX: Kajian Psikologi Sastra - Jelita Rahayu, Ema; Sam’un, Ahmad; Fahmi, Farizan (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to describe and analyze the personality of the main character, Ondeng, in Rudy Gunawan FX’s novel Jembatan Pensil through a literary psychology approach. The analysis employs Sigmund Freud’s psychoanalytic theory, which consists of the id, ego, and superego. A qualitative descriptive method was applied, using documentation and literature review as data collection techniques. The data analyzed were narrative quotations portraying the psychological conditions of the protagonist. The findings reveal that Ondeng’s personality is predominantly influenced by the id, reflected in spontaneous impulses and escapist fantasies. The ego appears in his realistic responses to social interactions, while the superego is evident in his moral attitudes, empathy, and social concern. A total of 20 id data, 3 ego data, and 12 superego data were identified. This study highlights the effectiveness of literary psychology in uncovering the depth of fictional characters and its pedagogical implications in literature learning.